HAK GRASI PRESIDEN DALAM SISTEM KETATANEGARAAN REPUBLIK INDONESIA - Mene, Meydianto; Prasetyanov, Yudha (Ensiklopedia of Journal, 2022)
Abstract: The right of clemency by the President as a prerogative/constitutional right in the Indonesian constitutional system still causes a lot of polemics. The right of clemency by the President is regulated in Article 14 paragraph (1) of the 1945 Constitution of the Republic of Indonesia, namely the President grants clemency and rehabilitation by taking into account the considerations of the Supreme Court. The application for clemency is regulated in Law no. 22 of 2002 jo. Law No. 5 of 2010 concerning Clemency. Before making a decision, the President must first consider the considerations of the Supreme Court.Keywords: Clemency Right, President.